The Effectiveness of Project-Based Learning Models to Train Vocational Skills of Students Majoring in Industrial Chemistry inVocational High School - Amelia, Rahadian Grace; Poedjiastoeti, Sri; Hidayat, Mohammad Thamrin (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study was to determine the effectiveness of the project-based learning model on laboratory-scale ethanol production material on the vocational skills of class X students majoring in Industrial Chemistry at SMK PGRI 1 Gresik. The effectiveness criteria are evaluated from student learning outcomes of students' vocational skills scores and student responses to project-based learning. This type of research is research and development (research and development / R&D) with field trials using one group pre-test post-test design. The research subjects were 40 students of SMK PGRI 1 Gresik. The instrument for measuring the effectiveness of project-based learning models on students' vocational skills is the vocational skills observation sheet and the student response questionnaire sheet. The data analysis technique used in this research is descriptive. The data obtained as follows: All students mastered vocational skills with the highest score obtained was 92.31. Student responses to project-based learning were 91%. Obstacles in carrying out learning activities are a limited number of tools and less time in carrying out experimental activities.Based on the results of data analysis, it can be concluded that the project-based learning model on laboratory-based ethanol-making materials is effective for training vocational skills of vocational students.